Karakterisitik Flow Patern Pada Aliran Dua Fase Gas-Cairan Melewati Pipa Vertikal - Priyo Heru Adiwibowo (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
Multi-phase flows are widely encountered in several engineering and industrial facilities, such as conventional steam power plants, evaporators and condensers, pressurized-water nuclear reactors, a wide variety of petroleum industries, chemicals and food processing industries. Surely, in the complex pipeline installation of these systems, vertical pipe will be commonly used for pipe connection. The purpose of this work is to investigate the flow pattern of gas-liquid two phase in the vertical pipe. Experiments will be performed in a 36 mm ID acrylic pipe vertical. Superifical liquid velocities and volumetric gas quality will be varied 0.3 1,1 m/s and 0.05 0.2 respectively. Digital camera will be used for flow pattern visualization in the vertical pipe. It was observed that effect of vertical pipe on flow pattern formed cluster bubbly flow for low volumetric gas quality with high superifical liquid velocities. For superifical liquid velocities with medium volumetric gas quality formed homogeneous bubbly flow and high volumetric gas quality is dense bubbly flow.